Temporal formulas in Serbian oral epic songs - Perić Dragoljub Ž. (Balcanica, 2013)
This paper seeks to present time as one of the most important parameters in epic songs, shown in the example of temporal formulas. Time also represents the principle of organizing section sequences in the song (linear, successive and chronological, or discontinuous and retrospective). The paper further examines the temporal formulas in a broad and a narrow sense, with regard to whether the temporal markers refer to the narrative shifts in the development of the story, or to some archaic meanings related to expressions which mark the determinants of real time (year and its parts, days of the week, time of the day, etc.).